A Qualitative Study on the Patriarchal Barriers to Healthcare Faced By Malaysian Indian Women In Kulim, Kedah Using Kabeer’s Theory of Empowerment - Saigaran, Nithiya Guna (Kajian Malaysia, 2026)
Health is influenced by gender and can have different impacts on women in society. Women from traditional households, particularly those from socioeconomically disadvantaged backgrounds, often experience neglect in their health, as it is considered less important. B40 Indian women are among the vulnerable groups, as they are part of patriarchal households that prioritise the health issues of men over their own. The term B40 refers to those with lower incomes, i.e., the bottom 40% of Malaysia’s income distribution. This study investigated patriarchal barriers to healthcare faced by Malaysian Indian women in Kulim, Kedah, Malaysia. Data were generated from semi-structured interviews with 25 participants selected through a purposive sampling technique. The data were analysed using Kabeer’s empowerment framework. The study’s findings included resource limitations, negotiations over Indian women’s agency, and distorted achievements in women’s health initiatives. The findings of this study contribute significantly to enlightening stakeholders on the efforts of B40 Malaysian Indian women to improve their health.